Genetic profiles of cervical tumors by high‐throughput sequencing for personalized medical care. (8th July 2015) - Muller, Etienne; Brault, Baptiste; Holmes, Allyson; Legros, Angelina; Jeannot, Emmanuelle; Campitelli, Maura; Rousselin, Antoine; Goardon, Nicolas; Frébourg, Thierry; Krieger, Sophie; Crouet, Hubert; Nicolas, Alain; et al.
<x xml:space="preserve">Abstract</x> Our laboratory has developed an oncogenic panel comprised of 226 genes to explore somatic mutations in cervical carcinomas, using high‐throughput sequencing and an automated dedicated bioinformatics pipeline. Besides recovering cervix uteri cancer mutational landscape, our results show that amongst all our patients, 48% display at least one deleterious mutation in genes already targeted by Food and Drug Administration approved therapies, and that 59% could be eligible for clinical trials. Here, we demonstrated that sequencing hundreds of genes in a clinical context is now feasible, useful for the diagnosis and treatment of cervix uteri cancer, and allows advancements towards personalized oncology.<boxed-text content-type="graphic" id="cam4492-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>